Blood lactate responses to cold water immersion and biking compared to controls in professional ice hockey players after high intensity skating - McCann, J.; Fowkes Godek, S.; McCrossin, J.; Raffa, S.; Morrison, K. (Journal of Athletic Training, 2012)
Context: Blood lactate recovery is important after high-intensity anaerobic exercise common to ice hockey. Previous research has investigated the effects of biking or cold-water immersion versus controls on post exercise recovery of blood lactate. However, a comparison study of cold-water emersion and biking treatments on blood lactate have not been evaluated in professional ice hockey players. Objective: To examine the effects of cold-water immersion (CWI), stationary cycling (Bike), and seated recovery (Control)after high-intensity skating on blood lactate levels immediately prior to treatment (pre-treatment) and at 5 (5-post), 10 (10-post) and 15 (15- post) min post treatment. We hypothesized that Bike would produce a greater reduction in blood lactate compared with CWI orControl. Design: Randomized Control Clinical Trial. Setting: Professional ice hockey training facility. Patients or Other Partici-pants: Sixty professional ice hockey players (age: 24.1 ± 5.2y weight: 90.5±7.5kg and height: 185±5.4cm) randomly divided into three experimental groups participated in the study. Interventions: Blood lactate was measured via fingerstick technique prior to and then immediately following an anaerobic on-ice 3 min skating test in full hockey equipment. After exercise, players immediately returned to the lockerroom, removed their equipment and reported to their assigned treatment which was either Control (15 min seated rest), CWI (8 min cold water at 11pC immersion to ASIS level and then 7 min standing) or Bike (15 min stationary cycling at 70% MHR). Blood lactate was measured by lactate analyzer (Accutrend) before and after exercise, and then immediately before treatment (pre-treatment) and at 5- post, 10-post and 15-post initiation of treatment. Main Outcome Measures: Blood lactate (mmol/l).Results: No differences in physical characteristics were found between groups. Blood lactate increased from baseline (3.1 ± 1.3 mmol/l) to post-exercise (11.4 ± 4 mmol/l), P< 0.001, however no differences were found between groups at baseline or post-exercise.At 5-post blood lactate was different from Control (9.7 ± 2.4 mmol/l) in Bike (7.9 ± 2.5 mmol/l) and CWI (7.7 ± 2.1 mmol/l), P=.01. There were no group differences at 10-post, P=.08, and only Bike (5.9 ± 2.6 mmol/l) was different from Control (8 ± 2.1 mmol/l) at 15-post, P = .02. Conclusions: The results suggest that after 5 min of treatment both biking and cold-water immersion facilitate a greater reduction in blood lactate compared to seated rest. After 15 min of treatment, only Bike was significantly different from Control, however, our research protocol included only 8 min of CWI because it is the typical length of time these players remain in cold water post exercise. Both Bike and CWI appear to facilitate the removal of lactate from the blood after high-intensity skating in elite ice hockey players however, additional research should evaluate a longer period of time for CWI post exercise.